Mobile applications and phygital concept in the retail sector in the function of enriching the shopping experience and developing CRM - Krajnović, Aleksandra; Živković, Marina; Ražov, Antonija (Oeconomica Jadertina, 2023)
This paper examines the issue of promotion in distribution chains and the current situation when it comes to the use of promotional tools in the distribution channel, as well as their combination, in the context of a multi-channel marketing strategy, as well as in enriching the user experience and CRM. The authors start from the thesis that new promotional tools, especially their use in the digital space, are less represented in retail chains compared to their use in the marketing of industrial manufacturers. The paper presents the conceptual framework related to the above-mentioned problem, and at the same time emphasizes the meaning of the optimal combination of online and offline promotional channels, which is of exceptional importance in the current era of the so-called phygital marketing. The paper focuses on mobile applications as a modern digital promotion channel, as well as their design, content and usage model on the examples of two shopping centers – Lidl and Kaufland, with a comparative analysis. Furthermore, the results of the primary research conducted on the segment of the consumer generation of young people are presented, which tried to find out their attitudes and opinions about the mentioned applications. In the last part of the paper, the author gives a critical review of the results, concluding remarks and guidelines for further research. The scientific contribution of the paper consists in the conceptualization of the use of mobile applications according to the model of Yadav & Pavlou (2020), who place the digitization of business at the center of marketing and business activities, and who in their model view promotional tools as the starting point for the development of long-term relationships with clients, primarily in the relations: company – client and client – company. The practical implications of the paper are reflected in the contribution to knowledge relevant to making strategic marketing decisions in trading companies and in the supply channel in general. The limitation of the research is the focus on the youth segment in the primary research, so for further research it is recommended to expand the analysis to other consumer segments, as well as to further develop the conceptualization of the scientific theory of marketing in the field of promotion and digitalization in the consumer goods trade sector.
Keywords: multi-channel marketing strategy; distribution chains; phygital concept; digital placement; phygital customer experience (PH-CX); mobile applications